ENSURING ECONOMIC DEVELOPMENT ON THE BASE OF OPTIMIZING THE ACTIVITY OF FARMS (Marketing Journal, 2026)
This study explores theoretical and practical approaches to optimizing the economic development of farming enterprises. It examines modern economic analysis methods aimed at optimal resource allocation, cost reduction, productivity improvement, and income maximization. The paper also provides recommendations for ensuring sustainable development, enhancing investment efficiency, and strengthening the competitiveness of farming enterprises based on economic modeling.
Keywords: farming enterprise; economic development; optimization; resource allocation; costs; productivity; income maximization; investment efficiency; economic models; sustainable development